Tax avoidance and firm value relationship in the listed companies of Bangladesh : a conceptual overview / Md. Nazrul Islam and Fathyah Hashim - Islam, Md. Nazrul; Hashim, Fathyah (Universiti Teknologi MARA, 2020)
The aim of the present paper is to look at whether corporate tax avoidance (CTA) contributes to firm value in the perspective of Bangladeshi listed firms. Our conceptual assumption is that in presence of agency conflicts, corporate managers take on tax avoidance (TA) initiatives to extract their own benefits through taking advantage as of the loopholes of current tax laws. Further, CTA does not fulfill the ethical and social demands. Agency costs and social irresponsibility that produce from TA activities could adversely influence the firm value. It is also among the first paper focusing on the TA and firm value association in the perspective of Bangladeshi listed firms after the gradual decline of stock market index during the year 2019, whereas most of the adjacent South Asian countries’ bourse has achieved gradual improve. However, the present paper aims to integrate relevant studies and theories to extend the intended potentials for limiting corporate tax avoidance to enhance the value of the listed companies in Bangladesh. This study has evaluated CTA behavior from a combination of agency theory and stakeholder theory standpoint rather than traditional sight of tax burden decreasing strategy. Moreover, as existing literature reveals inconsistent and less evidence that attempt to examine the consequence of CTA on firm value, the present paper proposes and shows an imperative proposition for potential empirical research.